Analisis Kepuasan Pelanggan dan Strategi Peningkatan Pelayanan pada PT. X dengan Metode Servqual dan QFD - Michelle Christina Linda Mulyawan; Jani Rahardjo; Prayonne Adi (Jurnal Titra, 2021)
Competition in the construction service industry rest on the company’s ability to provide service quality that satisfies customer expectations. Measurement of service quality with intangible characteristics can be done by measuring the level of customer satisfaction as an evaluation to improve service quality. Service quality is a method for measuring gap between customer perceptions and expectations of the service attributes. Evaluation of service quality are divided into five dimensions comprising of tangibles, reliability, responsiveness, assurances, and empathy. The negative value gap indicates that the customer satisfaction level is still less than the level of interest for the service attributes. The Quality Function Deployment (QFD) method will be used to translate and formulate service improvement strategies in efforts to reduce gaps that occur and improve customer satisfaction. This research is conducted using a chain analysis method consisting of three House of Quality levels to give more specific results for the company.